2011
DOI: 10.1007/s10162-011-0267-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression of Lgr5, a Wnt Target Gene, in the Developing and Mature Mouse Cochlea

Abstract: The Wnt signaling pathway is a recurring theme in tissue development and homeostasis. Its specific roles during inner ear development are just emerging, but few studies have characterized Wnt target genes. Lgr5, a member of the G protein-coupled receptor family, is a Wnt target in the gastrointestinal and integumentary systems. Although its function is unknown, its deficiency leads to perinatal lethality due to gastrointestinal distension. In this study, we used a knock-in reporter mouse to examine the spatiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
143
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 60 publications
15
143
1
Order By: Relevance
“…S4), comparable to the levels observed in the E14.5 base. This pattern of activity was similar to that in reporter mice for Lgr5, a target of Wnt/-catenin signaling (Chai et al, 2011).…”
Section: Canonical Wnt Signaling Is Active In the Developing Mammaliasupporting
confidence: 72%
See 1 more Smart Citation
“…S4), comparable to the levels observed in the E14.5 base. This pattern of activity was similar to that in reporter mice for Lgr5, a target of Wnt/-catenin signaling (Chai et al, 2011).…”
Section: Canonical Wnt Signaling Is Active In the Developing Mammaliasupporting
confidence: 72%
“…S1) and this pattern is maintained during postnatal stages (Simonneau et al, 2003). Recent analysis of reporter mice for downstream targets of Wnt/-catenin signaling (Chai et al, 2011) has suggested that this pathway might be active in the developing cochlea. In this study, we identify and characterize a dual role for Wnt/-catenin signaling during proliferation of the cochlear prosensory domain and during mechanosensory HC differentiation.…”
Section: Introductionmentioning
confidence: 94%
“…P2 cochleae were then cultured and treated with DAPT (P2-P5) in the presence of EdU. In the DMSO-treated control, tdTomato expression was observed at day 5 in the SC subtypes, as previously reported (37). Neither EdU…”
Section: /Myo7asupporting
confidence: 57%
“…GER cells are immediate neighbors of IBCs, IPhCs, and IHCs and may be less differentiated than SCs in the organ of Corti. GER cells exhibit higher levels of Wnt signaling (e.g., β-catenin and Lgr5) (38)(39)(40)52) and lower levels of Notch signaling (53) and respond readily to Atoh1 (atonal homolog 1) ectopic expression (54)(55)(56)(57). GER cells also express Nestin, a stem/progenitor cell marker in the central nervous system (58).…”
Section: Discussionmentioning
confidence: 99%
“…We used leucine-rich repeat-containing G-protein coupled receptor 5 (Lgr5)CreER T2 ;Rosa26 DTA (Lgr5DTA) mice induced at P0 and P1 to ablate IBCs, IPhCs, a small population of GER cells (two or three rows of cells in the lateral GER close to the IHCs), and some inner PCs (IPCs) and DCs (Fig. S1C, targeted cells are shown in red) (34,(38)(39)(40)(41)(42). We also used GlastCreER T ;Rosa26 DTA (GlastDTA) mice to target IBCs, IPhCs, and a broader mosaic cell population of the entire GER after tamoxifen treatment at P0 and P1.…”
Section: Neonatal Ibc/iphc Ablation Does Not Impact Adult Spiral Gangmentioning
confidence: 99%